2012
DOI: 10.1189/jlb.1011497
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Advance: Protein synthesis modulates responsiveness of differentiating and malignant plasma cells to proteasome inhibitors

Abstract: A previously unsuspected, considerable proportion of newly synthesized polypeptides are hydrolyzed rapidly by proteasomes, possibly competing with endogenous substrates and altering proteostasis. In view of the anti-cancer effects of PIs, we set out to achieve a quantitative assessment of proteasome workload in cells hallmarked by different PI sensitivity, namely, a panel of MM cells, and in a dynamic model of plasma cell differentiation, a process that confers exquisite PI sensitivity. Our results suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 54 publications
9
89
0
1
Order By: Relevance
“…Accumulating evidence has linked protein synthesis to the responsiveness of proteasome inhibitors in multiple myeloma. [55][56][57][58] Moreover, proteasome inhibitors were shown to trigger the protein kinase RNA-like endoplasmic reticulum kinase-dependent branch of the unfolded protein response and CHOP, leading to a terminal ER stress response due to accumulation of unfolded proteins. [57][58][59] Here, we demonstrated that isolated truncated gHCs are poorly secreted by plasma cells, which in turn, are intrinsically and basically stressed as observed by overexpression of CHOP and XBP1s.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has linked protein synthesis to the responsiveness of proteasome inhibitors in multiple myeloma. [55][56][57][58] Moreover, proteasome inhibitors were shown to trigger the protein kinase RNA-like endoplasmic reticulum kinase-dependent branch of the unfolded protein response and CHOP, leading to a terminal ER stress response due to accumulation of unfolded proteins. [57][58][59] Here, we demonstrated that isolated truncated gHCs are poorly secreted by plasma cells, which in turn, are intrinsically and basically stressed as observed by overexpression of CHOP and XBP1s.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Briefly, cells were sonicated in icecold buffer (50 mM Tris-HCl [pH 7.5], 1 mM DTT, 0.25 M sucrose, 5 mM MgCl 2 , 0.5 mM EDTA, 2 mM ATP), and extracts were prepared by centrifugation (30 min 10,000 g, and 15 min 100,000 g). Proteasome-specific chymotryptic peptidase activity was assayed by monitoring the production of 7-amino-4-methylcoumarin (amc) from 100 mM Suc-LLVY-amc (Bachem, I-1395) in 20 mM Tris-HCl (pH 7.5), 1 mM ATP, 2 mM MgCl 2 , 0.2% bovine serum albumin.…”
Section: Sqstm1 Immunoprecipitationmentioning
confidence: 99%
“…4 This load-versus-capacity model contributes to explain PI sensitivity in malignant PCs, as myelomas with high proteasome capacity and low proteasome workload show relative primary resistance. 5 Indicative of cause-effect relationships, both increasing proteasome expression 5 and attenuating protein synthesis 6 specifically reduced vulnerability of myeloma cells to the first-in-class PI bortezomib.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of proteasomes were also observed in acute lymphocytic leukemia, T-cell leukemia, and acute myelocytic leukemia cells (13). It is thought that the high level of proteasome activity in cancer cells provides survival benefits under the stress of continued cell proliferation (14,15).…”
Section: Introductionmentioning
confidence: 99%